THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF TEAM ASSISTED INDIVIDUALIZATION (TAI) TYPE AND STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TYPE TOWARD MATHEMATICS LEARNING OUTCOMES - Sharah Mita Sukmawati; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning in school is still dominated by the teacher, causing a lack of involvement of the student in participating in learning activities and have difficulty in understanding the material. This study aims to determine the effectiveness of the use of cooperative learning model type TAI and STAD on the results of student's mathematics learning in class VIII SMP Negeri 1 Kretek Bantul Academic Year 2015/2016. The population in this study were all students of class VIII SMP Negeri 1 Kretek Bantul consists of 6 classes. The sampling technique using random sampling techniques, derived class VIII B as the experimental class I (TAI), VIII D as the experimental class II (STAD), and VIII C as the control class. Designs in this study using Posttest-Only Control Design. The data collection technique using the test method. Instrument test using validity test and reliability test. Test requirements analysis includes tests of normality and homogeneity test. Analysis of data to test the hypothesis using analysis of variance and LSD test. Results of analysis of variance with a significance level of 5% and df = (2,79) show that: (1) there is a difference between the results of the students' mathematics learning using learning model type TAI, STAD learning model, with the conventional learning models. This is indicated by the value and  and ,  then  rejected and (2) learning model type TAI and STAD more effective than conventional learning models on the results of students' mathematics learning. This is indicated by the results of LSD in case I  and LSD = 8,84, consequently  so  accepted. In Case II  and LSD = 8,76, consequently  so  rejected. While in case III |  and LSD = 8,76, consequently  so  rejected. It can be concluded .